2015
DOI: 10.4049/jimmunol.1500552
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the SLAM Adapter Molecule EAT-2 as a Lupus-Susceptibility Gene That Acts through Impaired Negative Regulation of Dendritic Cell Signaling

Abstract: We showed previously that C57BL/6 congenic mice with an introgressed homozygous 70 cM (125.6 Mb) to 100 cM (179.8 Mb) interval on c1 from the lupus-prone New Zealand Black (NZB) mouse develop high titers of antinuclear Abs and severe glomerulonephritis. Using subcongenic mice, we found that a genetic locus in the 88–96 cM region was associated with altered dendritic cell (DC) function and synergized with T cell functional defects to promote expansion of pathogenic proinflammatory T cell subsets. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Studies in lupus-prone mice have revealed numerous B and T cell tolerance defects that contribute to autoantibody production [13,23,29,43]; however, the manner in which these tolerance defects reinforce one another, and the critical point at which the balance tips to autoimmunity, remains unclear. In this study, we show that mice with the 96–100 cM interval from NZB chromosome 1 breach anergy to the neo-self antigen HEL, with significantly higher levels of anti-HEL Abs and antibody-producing cells compared with their non-autoimmune B6 counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in lupus-prone mice have revealed numerous B and T cell tolerance defects that contribute to autoantibody production [13,23,29,43]; however, the manner in which these tolerance defects reinforce one another, and the critical point at which the balance tips to autoimmunity, remains unclear. In this study, we show that mice with the 96–100 cM interval from NZB chromosome 1 breach anergy to the neo-self antigen HEL, with significantly higher levels of anti-HEL Abs and antibody-producing cells compared with their non-autoimmune B6 counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the opportunity to assess the relative and temporal contribution of different DC populations to the development of specific disease manifestations, mouse models also allow for the identification of specific processes in DCs which affect disease development. Targeted deletion of regulatory molecules associated with SLE susceptibility in humans, including Shp1, A20, Blimp-1, Lyn, or Eat-2, specifically in CD11c + cells resulted in increased DC activity and development of inflammatory and autoimmune phenotypes characterized by the production of autoreactive antibodies and several manifestations of SLE, including severe glomerulonephritis [ 128 132 ].…”
Section: The Role Of Dcs In Mouse Sle Modelsmentioning
confidence: 99%
“…T:B interactions regulated by SAP and Ly108 ( Slamf6 ) as well as CD84 ( Slamf5 ) are necessary for GC formation [62]. Mutations in SLAM family genes [63] as well as in EAT-2 [64] have been associated with lupus susceptibility in mice. The SLAM family genes are arranged in a cluster in tight linkage disequilibrium, and it has been difficult to delineate the contribution of each gene to the autoimmune process [65].…”
Section: Regulation Of T:b Cell Interaction By Slam Family Genesmentioning
confidence: 99%